Analysis of heterogeneous energy demand in transportation sector in Thailand - Patoomnakul, Atchara; Daloonpate, Apichart; Mahathanaseth, Itthipong; Premashthira, Aerwadeee (Kasetsart Journal of Social Sciences, 2021)
This study was conducted to analyze the energy demand for each income group in Thailand using the QUAIDS model and to estimate the welfare effect of carbon tax based on the compensating variation. The estimated own-price elasticities of demand for gasoline and diesel were elastic, whereas those for gasohol and LPG were inelastic. These results reflect the responsiveness of Thai households to changes in energy policies. The compensating variations for the household income groups showed that the carbon tax was progressive. The poor were more affected by the carbon tax than the rich, and farmers suffered the worst economic loss compared to other groups. Therefore, the government should show some discretion in designing and implementing energy policies.